DETERMINAN KEJADIAN STUNTING DI ASIA TENGGARA : META ANALISIS - Fitri, Sri Ramadhani (LPPM Universitas Awal Bros, 2025)
​​ The problem of stunting (short children) is one of the nutritional problems faced by the world, especially in poor and developing countries. Stunting is a health problem because it is associated with the risk of morbidity and mortality. In 2017, 22.2% or around 150.8 million children under five in the world were stunted. The purpose of this study is to find out what are the determinants of stunting in Southeast Asia using the Meta-analysis research method with analysis of fixed effects models and random effects models. An observational research study site from International articles located in Southeast Asia from 2000-2022. Journals were collected using data based: Google Scholar, Pubmed, Springer Link and Science Direct. The results of the identification of articles were obtained as many as 24 relevant articles entered the meta-analysis stage. The results showed that family income OR 3.26 (95% CI: 1.77-599), LBW OR 2.70 (95% CI: 2.09-3.49), Mother's education OR 1.94 (95% CI : 1.44-2.63) and environmental sanitation OR 1.71 (95% CI: 1.54-1.89). The most influential variable on the determinants of stunting in Southeast Asia is the family income variable. One of the efforts that can be done is to prioritize health promotion with attractive and easily understood media by the public, thereby increasing public awareness of stunting prevention and control efforts